The Effect Vitamin C Enriched Pellets to Increase the Immunity of Oreochromis niloticus - Maytra Wirdona; Morina Riauwaty; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTVitamin C is a nutrient that is soluble in water and is essential for life as well as for maintaining health, enhancing immunity of fish in fighting infections and as an antioxidant. The study aims to obtain the best dose of vitamin C on total leukocytes, leukocyte differentiation, and phagocytosis activity to increase the immunity of nile tilapia towards disease attack Streptcoccosis. The method used is the experimental method by using the full random draft (RAL) One factor with five levels of treatment and the treatment is repetead three times. After the treatment was applied, namely Kn (without vitamin C enriched pellets and not challenged), Kp (pellets without vitamin C enriched and challenged), vitamin c enriched pellets at a dose of P1 (1 g/kg and challenged with Streptococcus agalactiae), P2 (1.5 g/kg and challenged with S. agalactiae), P3 (2 g/kg and challenged with S. agalactiae). Nile tilapia used in size 8-10 cm with solid tebar 1 tail/3 L water is maintained in the aquarium with a size of 40 x 30 x 30 cm with a feed enriched with vitamin C for 46 days. The fish was challenged with S. agalactiae with a density 108 CFU/mL at the dose of 0.1 mL/tail intramuscular on day 32 after that the fish re-maintained until the 46 days. Measured parameters are total leucocytes, leucocyte differentiation, phagocytic activity and survival rate of nile tilapia. The results shown that the feed enriched with vitamin C and tested with S. Agalactiae has an influence on the immunity of fish with the best treatment in P3 (the vitamin C enriched pellets at a dose of 2 g/kg and challenged) with an average total leukocytes was 8.02 x 104 cells/mm3, lymphocytes were 84.67%, neutrophils was 8.67%, monocytes were 6.66%, phagocytosis activity is 46.00% and the livelihood reaches 93.33%.Keywords : Leukocytes, Tilapia, Vitamin C, Streptococcus agalactiae, Phagocytosis